1992
DOI: 10.1177/0013916592245006
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Privacy and Different Components of Job Satisfaction

Abstract: The level of workspace architectural privacy has previously been found to relate to overall job satisfaction. It was hypothesized that because privacy may serve particular functions, only particular facets of job satisfaction will be related to it, both in the short term (less than 1 year) and in the long term (more than 1 year). One hundred thirty professional secretaries assessed their level of privacy and their level of job satisfaction as measured by the Minnesota Satisfaction Questionnaire. The results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Reflecting on such data, Baldry and colleagues observe that despite declarations of employee commitment and empowerment, the 'tight physical and technological surveillance' of the modern office is a major contributor to employee disenchantment (1998a, p. 175). Consistent with this claim, in a study of 130 secretarial staff, Duvallearly and Benedict (1992) found a strong relationship between the low levels of privacy afforded in open-plan offices and key components of job dissatisfaction.…”
Section: Problems With Dominant Approaches To Space Management and Dementioning
confidence: 76%
See 1 more Smart Citation
“…Reflecting on such data, Baldry and colleagues observe that despite declarations of employee commitment and empowerment, the 'tight physical and technological surveillance' of the modern office is a major contributor to employee disenchantment (1998a, p. 175). Consistent with this claim, in a study of 130 secretarial staff, Duvallearly and Benedict (1992) found a strong relationship between the low levels of privacy afforded in open-plan offices and key components of job dissatisfaction.…”
Section: Problems With Dominant Approaches To Space Management and Dementioning
confidence: 76%
“…For if managers are charged with creating standardized working conditions, then opportunities for autonomy become necessarily restricted (Elsbach, 2004;Hyer and Wemmerlov, 2002;Sewell and Wilkinson, 1992). As a result, several commentators argue that the best that workers can hope for is to have a sense of involvement in the decisions affecting their workspace (Duvallearly and Benedict, 1992;Rose and Wright, 2005).…”
Section: Dominant Approaches To Space Management and Designmentioning
confidence: 99%
“…Research indicates that employees working in traditional and private office rooms have higher levels of satisfaction with their workplace and job compared to employees in open‐plan offices (Birnholtz, Gutwin, & Hawkey, ; Duval, Veitch, & Charles, ). Duvall‐Early and Benedict (), however, did not find any relationship between perceived privacy and satisfaction with work environments.…”
Section: Open‐plan Office Design and Today's Industriesmentioning
confidence: 89%
“…Although privacy is the condition of the individual (Chapin, 1951;Westin, 1967;Weiss, 1983;Schoeman, 1984;Gavison, 1984;Newell, 1998), the environment in which the individual exists is also related to the concept of privacy (Chermaye¡ & Alexander, 1963;Hall, 1969;Canter & Canter, 1971;Duvall-Early & Benedict, 1992). The de¢nition of privacy varies for each individual due to di¡erent personal characteristics, cultural backgrounds, sex, age, economical, educational and social backgrounds (Altman, 1975(Altman, , 1976(Altman, , 1977Newell, 1994Newell, , 1995Newell, , 1998.…”
Section: Privacy Requirements In a Design Studiomentioning
confidence: 99%